The place of truth in a world of evidences:: The rethoric o f biomedical Sciences (Iter, 2022)
This article develops some aspects o f the notion o f evidence or p ro o fin the so-called biomedical Sciences, emphasizing that they constitutecommunities o f methods rather than o f truths. The notion o f truth in anabsolute sense is absent from the scientific discourse and is replaced bythe vague term “evidence ” in its least concrete connotations. This means adisplacement from goals or ends o f knowledge to the means which permitits construction. Some implications o f this scenario indícate the need o f adialogical perspective in the social construction o f knowledge aasociatedwith the professions related to health and healthcare.
Keywords: Evidence, medicine, dialogue